PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, PROFITABILITAS, LEVERAGE, UKURAN DEWAN KOMISARIS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2013-2015) - Dina Restuti Dewi, 13.05.52.0169; Maryono, Maryono (Students' Journal of Accounting and Banking, 2017)
The purpose of this study is to examine the effect of Company Size, Liquidity, Profitability, Leverage, Size of Board of Commissioners and Institutional Ownership to Disclosure of Corporate Social Responsibility to Manufacturing Companies listed on Indonesia Stock Exchange. The dependent variable in this study is the disclosure of Corporate Social Responsibility and the independent variables are company size, liquidity, profitability, leverage, boardsizeand institutional ownership. The population in this study are all Manufacturing Companies listed in Indonesia Stock Exchange in 2013-2015. A total of 239 samples were met as criteria of this study. This research uses purposive sampling method. The technique of data testing is by using multiple linear regression analysis. The result of the analysis shows that the variables that have significant positive influence are liquidity, board size and institutional ownership, while firm size,profitability and leverage variable has a positive effect is insignificant affect the disclosure of Corporate Social Responsibility in Manufacturing company listed in Indonesia Stock Exchange in 2013 -2015.Keywords: Firm Size, Liquidity, Proftitability, Leverage, Size of Board of Commissioner, and Institusional Ownership and Corporate Social Resposibility Disclosure